Java 17 Quick Syntax Reference A Pocket Guide to the Java SE Language, APIs, and Library. - Olsson, Mikael (Apress L. P., 2021)
Quickly gain the insight necessary to address a multitude of Java coding challenges using this succinct reference guide, Java 17 Quick Syntax Reference, Third Edition . Short, focused code examples will help you learn and master various existing and new Java source code elements. This edition includes the following additions to Java SE and OpenJDK, through Java 17: Pattern matching for switch and instanceof, Sealed classes and interfaces, Switch expressions, Text block multiline strings, Java module system, Private methods in interfaces, and Type inference for local variables. You won't find any technical jargon, bloated samples, drawn out history lessons or witty stories in this book. What you will find is a language reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any Java programmer. What You Will Learn Run a Java file with a single command Learn what a switch expression is and how to use it Use pattern matching Code with Java modules Create text blocks to handle multiline strings Learn what sealed classes are and how to use these and more Who This Book Is For Those with prior experience with Java who want a quick and handy reference.